2013
DOI: 10.1007/s10792-013-9729-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of primary selective laser trabeculoplasty in patients with primary open-angle glaucoma

Abstract: To determine if primary selective laser trabeculoplasty (SLT) can be repeated with clinical benefit in patients with primary open-angle glaucoma (POAG). Forty-two eyes of 42 patients with POAG were studied. All patients underwent primary SLT treatment of 40-50 shots to the trabecular meshwork over 360°. The treatment response at the initial post-SLT visit (4 weeks), and second post-SLT visit (mean 4 months), clinical success and duration of clinical success were measured. SLT was repeated in all patients after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 16 publications
3
49
0
1
Order By: Relevance
“…1 To date, only 2 studies reported the results of repeat SLT after failed SLT; none of these studies reported PAS. 7,8 To our knowledge, this is the first report to demonstrate PAS as a late complication of repeat SLT. Both of our patients had undergone successful and uneventful SLT 3 and 4 years ago by the same surgeon performing the repeat SLT.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…1 To date, only 2 studies reported the results of repeat SLT after failed SLT; none of these studies reported PAS. 7,8 To our knowledge, this is the first report to demonstrate PAS as a late complication of repeat SLT. Both of our patients had undergone successful and uneventful SLT 3 and 4 years ago by the same surgeon performing the repeat SLT.…”
Section: Discussionmentioning
confidence: 63%
“…3 Unlike ALT, SLT has the theoretical advantage of being more repeatable because it uses about 100 times less energy than ALT and causes minimal damage to the trabecular meshwork with no subsequent contractile laser scars. [7][8][9] SLT is considered a low-risk procedure. The most frequent adverse effects are transient IOP spike, mild anterior chamber inflammation, photophobia, and conjunctival hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…Looking close at the more recent literature, one can note several studies showing that SLT can be repeated with similar efficacy when compared to the first SLT treatment. In these studies, POAG patients presented a significant IOP reduction at 1 (46) , 4 (47) , 6 (46) , 12 (19,48) , 15 (46) , and 24 months after repeating SLT (26,49) . Corroborating these findings, Gandolfi and Ungaro demonstrated that repeated low power SLT as initial treatment postponed the initiation of medical therapy by a mean time of 6.2 years in patients with OHT (19) .…”
Section: Safety Duration and Repeatabilitymentioning
confidence: 90%
“…Some success predictors are well established. For instance, better results are usually observed in patients with POAG (33,37,(51)(52)(53)(54)(55)(56) , pseudoexfoliative glaucoma (31,40,57,58) , and higher baseline IOP (40,41,46,47) . A few isolated studies observed better results in eyes with thinner corneas (59) , with earlier disease stage (60) , and with higher refractive errors (52) .…”
Section: Success Predictors Of Selective Laser Trabeculoplastymentioning
confidence: 99%
See 1 more Smart Citation